2022
DOI: 10.21873/invivo.13038
|View full text |Cite
|
Sign up to set email alerts
|

Poor Prognosis With Intravesical Bacillus Calmette-Guérin History After Photodynamic Diagnosis-assisted Transurethral Resection Using 5-Aminolevulinic Acid

Abstract: Background/Aim: Diagnostic efficacy and treatment outcome of orally administered 5 aminolevulinic acid (ALA) assessment for photodynamic diagnosis (PDD) in transurethral resection for non-muscle-invasive bladder cancer (NMIBC) in clinical practice. Patients and Methods: A retrospective analysis was performed of 105 patients who underwent PDD transurethral resection using orally administered ALA and were pathologically diagnosed with Ta, T1, or Tis at the Ishikawa Prefectural Central Hospital from December 2018… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
(19 reference statements)
0
0
0
Order By: Relevance
“…In the BCG combination therapy group, the presence or absence of PDD did not show a significant difference in 2-year progression-free survival, and PDD did not affect disease progression control [112]. Makino et al revealed that prior BCG infusion history, particularly BCG-unresponsive disease, is responsible for poor prognostic factors in NMIBC patients undergoing PDD-TURBT [115]. Thus, special postoperative follow-up may be needed for these patients.…”
Section: Pdd With 5-ala For Turbt In Nmibcsmentioning
confidence: 99%
“…In the BCG combination therapy group, the presence or absence of PDD did not show a significant difference in 2-year progression-free survival, and PDD did not affect disease progression control [112]. Makino et al revealed that prior BCG infusion history, particularly BCG-unresponsive disease, is responsible for poor prognostic factors in NMIBC patients undergoing PDD-TURBT [115]. Thus, special postoperative follow-up may be needed for these patients.…”
Section: Pdd With 5-ala For Turbt In Nmibcsmentioning
confidence: 99%